2020
DOI: 10.1016/j.mayocp.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mortality of COVID-19 Patients With Gastrointestinal Symptoms: A Systematic Review and Meta-analysis

Abstract: Objective: To perform a systematic review and meta-analysis evaluating the prevalence of gastrointestinal (GI) symptoms and mortality in patients with coronavirus disease 2019 (COVID-19) diagnosed. Methods: A systematic search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus was performed from December 1, 2019 to May 7, 2020. Observational studies including adults with COVID-19 infection and reporting GI symptoms were included. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 62 publications
8
98
3
6
Order By: Relevance
“…( 24 ) Another systematic review and meta-analysis which included 12,797 patients reported that mortality in the group of patients with GI symptoms (0.4% [IC95%, 0-1.1%; I 2 = 74%]) was similar ( p = 0.15) to overall mortality (2.1% [IC95%, 0.2-4.7%; I 2 = 94%]). ( 25 )…”
Section: Discussionmentioning
confidence: 99%
“…( 24 ) Another systematic review and meta-analysis which included 12,797 patients reported that mortality in the group of patients with GI symptoms (0.4% [IC95%, 0-1.1%; I 2 = 74%]) was similar ( p = 0.15) to overall mortality (2.1% [IC95%, 0.2-4.7%; I 2 = 94%]). ( 25 )…”
Section: Discussionmentioning
confidence: 99%
“…Since gastrointestinal symptoms mainly occur before respiratory and systemic involvement, 124,125 several authors evaluated whether digestive symptoms occurrence represents an unfavorable prognostic factor. 76,100,126 In a pivotal metanalysis on 4 studies, Gul et al 127 (95% CI, 0% to 1.1%). 76,100,126 On the other hand, the occurrence of gastrointestinal symptoms may be useful in predicting nasopharyngeal swab positivity (OR 1.7).…”
Section: Association Of Symptoms With Severity and Mortalitymentioning
confidence: 99%
“…76,100,126 In a pivotal metanalysis on 4 studies, Gul et al 127 (95% CI, 0% to 1.1%). 76,100,126 On the other hand, the occurrence of gastrointestinal symptoms may be useful in predicting nasopharyngeal swab positivity (OR 1.7). 73…”
Section: Association Of Symptoms With Severity and Mortalitymentioning
confidence: 99%
“…The role of COVID-19 in the pathogenesis of gastrointestinal symptoms associated with viral infections has been the subject of a number of publications, many reporting a high prevalence of nausea, vomiting, abdominal pain, diarrhea and anorexia) [ [2] , [3] , [4] ]. More importantly, fecal viral shedding of SARS-CoV-2 is a potential transmission mechanism currently under investigation [ 5 ].…”
mentioning
confidence: 99%
“…Only two patients had previous chronic liver disease, and the global mortality rate reached 7.1%. While there is no conclusive evidence thus far of a specific mechanism causing liver damage from COVID-19, at least five theories have been proposed: [ 1 ] direct cytopathic damage [ 2 ], systemic inflammatory response [ 3 ], liver hypoxia and ischemia [ 4 ], acute-on-chronic liver injury, and [ 5 ] drug-induced liver injury [ 11 ]. We are barely beginning to understand the dynamics of COVID-19, and therefore additional clinical and epidemiological data are needed in order to develop risk predictors, identify high-risk populations, and propose new public-health policies.…”
mentioning
confidence: 99%